Home sweet Christmas - Mallery, Susan (Toronto, Ontario, Canada : HQN, 2022)
Excited to regain her independence after sending her sisters off to college, Camryn isn$1 (Bt thrilled when a client sets her up with her son.s
Sequel to: The Christmas wedding guest.
Keywords: Man-woman relationships -- Fiction; Hotelkeepers -- Fiction; Sisters -- Fiction; Small cities -- Fiction; Secrecy -- Fiction; Washington (State) -- Fiction; Christmas fiction; Romance fiction